Self-Reported Prevalence of Chronic Diseases and Their Relation to Selected Sociodemographic Variables: A Study in INDEPTH Asian Sites, 2005 - Hoang Van Minh, MD, PhD; Nawi Ng, MD, PhD; Uraiwan Kanungsukkasem; Peter Byass, PhD; Kusol Soonthornthada; Tran Huu Bich, MD, PhD; Ali Ashraf, MPH; Abdullahel Hadi, MD, PhD; Sanjay Juvekar, PhD; Abdur Razzaque, MD, PhD (Centers for Disease Control and Prevention, 2008)
IntroductionLack of reliable population-based data, especially morbidity data, is a barrier to preventing and controlling chronic diseases in developing countries. We report the self-reported prevalences of major chronic diseases in Southeast Asia and examine their relation to selected sociodemographic variables in adults.MethodsData are from a 2005 cross-site study of 8 sites in 5 Asian countries that surveyed 18,484 people aged 25-64 years. Respondents were asked whether they had been told by a health care worker that they had any of 7 chronic health conditions: joint problems, stroke, heart disease, diabetes, pulmonary disease, hypertension, or cancer. Information about participants' sex, age, and educational level was also obtained.ResultsWe found that 22.7% of men and 31.6% of women reported having at least 1 of the chronic health conditions of interest, and 5.1% of men and 9.2% of women reported having 2 or more chronic conditions. Multivariate regression analyses showed that women had more chronic conditions than men, the prevalence of chronic conditions increased with age, and people with the least education were more likely to have chronic conditions.ConclusionChronic conditions are commonly reported among adults in Asian countries. Disparities in the prevalence of chronic conditions by sex and education are evident.